The Future of Bali’s Kerauhan Tradition: Legal Pluralism, Reforms, and Conflict Adjudication Challenges - Praditha Dewa Gede Edi; Rahayu Mella Ismelia Farma; Perbawa I Ketut Sukewati Lanang Putra; Paul Atagamen Aidonojie; Adelowo Stephen Asonibare (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
This study analyzes the regulation of the kerauhan tradition in Bali within the framework of legal pluralism from a legal anthropological perspective. Balinese customary law conceptualizes kerauhan as a sacred and non-pathological spiritual phenomenon intended to preserve communal harmony and cosmic balance, whereas the national legal system is constructed upon empirical verification and rational causation. This distinction gives rise to a fundamental epistemological divergence between customary and state legal orders. The research applies an empirical juridical method with a qualitative design. It gathers data through in depth interviews with customary leaders, direct observation of ritual practices, and systematic analysis of relevant awig awig provisions. This approach enables a contextual evaluation of how plural legal systems operate in addressing incidents related to kerauhan. The findings indicate that: first, Balinese customary law recognizes and regulates kerauhan as a legitimate sacred mechanism grounded in spiritual authority and communal belief, rather than as a pathological act; second, a structural and epistemological disparity between customary and national law produces legal tension, particularly because customary dispute resolution relies on ritual validation while state institutions require material evidence and objective causation, thereby creating complexity in cases involving bodily injury or property damage; and third, modernization and tourism have commodified kerauhan, transforming it into a public spectacle and digital media content, which gradually reshapes its social meaning and influences generational perceptions. The study concludes that the development of a responsive and integrative pluralistic legal framework is necessary to accommodate indigenous epistemology while ensuring legal certainty, accountability, and substantive justice.